2021
DOI: 10.1111/sed.12932
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization processes in modern calcareous tufa: Possible roles of viruses, vesicles and extracellular polymeric substances (Corvino Valley – Southern Italy)

Abstract: A modern lithifying biofilm, associated with fluvial calcareous tufa in southern Italy, is composed of a complex community of micro‐organisms including autotrophic and heterotrophic bacteria, together with likely viruses (bacteriophages) and bacterial vesicles. Produced by most of the bacterial forms, extracellular polymeric substances are widespread and are the main sites of mineral precipitation, rather than the microbial cells themselves, but viruses and vesicles also appear to be mineralized. Neoformed bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 125 publications
0
11
0
Order By: Relevance
“…On the other hand, the presence of Alcaligenes sp. promotes the generation of stable corrosion products Fe 2 O 3 and Fe 3 O 4 , and EPS is an ideal nucleation site for mineral deposition, which can be used as a binding site for Ca 2+ and Mg 2+ , leading to the deposition of calcite structured CaCO 3 and Mg (OH) 2 minerals (Spadafora et al, 2010;Perri et al, 2022). Therefore, the impedance film value of the Alcaligenes sp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of Alcaligenes sp. promotes the generation of stable corrosion products Fe 2 O 3 and Fe 3 O 4 , and EPS is an ideal nucleation site for mineral deposition, which can be used as a binding site for Ca 2+ and Mg 2+ , leading to the deposition of calcite structured CaCO 3 and Mg (OH) 2 minerals (Spadafora et al, 2010;Perri et al, 2022). Therefore, the impedance film value of the Alcaligenes sp.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of authigenic Mg‐clays, including t‐smectite (stevensite and kerolite) and palygorskite‐sepiolite, have been observed to have formed in association with carbonate and EPS in saline and alkaline lacustrine and marine environments (e.g. Calvo et al, 1999; Eardley, 1938; Leguey et al, 2010; Léveillé et al, 2002; Perri et al, 2022). Microbially influenced mineralisation of other silicates, such as Al and Fe silicates, has also been demonstrated in different environments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hollow spheres composed of dolomite nanocrystals may Folk, 1993;Van Lith et al, 2003;Vasconcelos & McKenzie, 1997), experimental observations by Bontognali et al (2008) found that EPS excreted from the cell wall was the main site of nucleation and mineralisation. Some 100 nm-sized nanospheroids could be permineralised bacterial vesicles and viruses, as described from modern tufa by Perri et al (2022).…”
Section: Spheroidal Dolomitementioning
confidence: 96%
“…In laboratory experiments, bacteriophages were also shown to likely influence vaterite formation -a metastable form of calcium carbonate (Słowakiewicz et al, 2021). A few studies have been conducted so far in relation to modern siliceous (Daughney et al, 2004;Laidler and Stedman, 2010;Peng et al, 2013), iron-rich (Kyle et al, 2008;Orange et al, 2011), carbonate (Pacton et al, 2015;Słowakiewicz et al, 2021;Perri et al, 2022), and microbial mat (De Wit et al, 2015;Perri et al, 2018;Pennafirme et al, 2019;Pacton et al, 2014;Carreira et al, 2015) environments. Therefore, in light of the abovementioned works, bacteriophages might play a role in various sedimentation processes.…”
Section: Framboids and Their Originmentioning
confidence: 99%